Receptor binding domain proteins of SARS‐CoV‐2 variants produced in Nicotiana benthamiana elicit neutralizing antibodies against variants of concern. Issue 9 (1st June 2022) - Khorattanakulchai, Narach; Manopwisedjaroen, Suwimon; Rattanapisit, Kaewta; Panapitakkul, Chalisa; Kemthong, Taratorn; Suttisan, Nutchanat; Srisutthisamphan, Kanjana; Malaivijitnond, Suchinda; Thitithanyanont, Arunee; Jongkaewwattana, Anan; Shanmugaraj, Balamurugan; Phoolcharoen, Waranyoo
Abstract: The constantly emerging severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2) variants of concerns (VOCs) with mutations in the receptor‐binding domain (RBD) spread rapidly and has become a severe public health problem worldwide. Effective vaccines and optimized booster vaccination strategies are thus highly required. Here, the gene encoding six different RBD (Alpha, Beta, Gamma, Kappa, Delta, and Epsilon variants) along with the Fc fragment of human IgG1 (RBD‐Fc) was cloned into plant expression vector and produced in Nicotiana benthamiana by transient expression. Further, the immunogenicity of plant‐produced variant RBD‐Fc fusion proteins were tested in cynomolgus monkeys. Each group of cynomolgus monkeys was immunized three times intramuscularly with variant RBD‐Fc vaccines at Day 0, 21, 42, and neutralizing antibody responses were evaluated against ancestral (Wuhan), Alpha, Beta, Gamma, and Delta variants. The results showed that three doses of the RBD‐Fc vaccine significantly enhanced the immune response against all tested SARS‐CoV‐2 variants. In particular, the vaccines based on Delta and Epsilon mutant RBD elicit broadly neutralizing antibodies against ancestral (Wuhan), Alpha, and Delta SARS‐CoV‐2 variants whereas Beta and Gamma RBD‐Fc vaccines elicit neutralizing antibodies against their respective SARS‐CoV‐2 strains. The Delta and Epsilon RBD‐Fc based vaccines displayed cross‐reactive immunogenicity and might be applied as a booster vaccine to induce broadly neutralizing antibodies. These proof‐of‐concept results will be helpful for the development of plant‐derived RBD‐Fc‐based vaccines against SARS‐CoV‐2 and its variants.